The Politics of Citizenship and Welfare: Countering “Extractivism” in Resource-Rich Regions in Indonesia - Tapiheru, Joash; Capri, Wigke; Lestariningsih, Dian; Nudya, Hening Kartika (Springer, 2022)
This chapter discusses the constitution of citizenship through the issue of welfare production/distribution in natural resource-rich regions. The issue of welfare production/distribution has been a central one in the democratisation and accompanying decentralisation of post-1998 Indonesia. Welfare has become a nodal point towards which every other issue is related (see, for example, Santoso et al. in Executive summary: Power, welfare, and democracy. Universitas Gadjah Mada and University of Oslo, Yogyakarta, 2014). As Indonesia is generally known for being endowed with a wealth of natural resources that have been subjected to exploitation for centuries, it is inevitable that the issue of welfare in the country has become closely associated with the issue of natural resource extractive industries and the distribution of the wealth they create. This chapter brings the issue of welfare to the forefront (Nordholt & Klinken in Politik lokal di Indonesia. KITLV-Jakarta dan Yayasan Obor Indonesia, Jakarta, 2007). More specifically, this chapter discusses the topic of welfare and welfare distribution as related to extractive industries, particularly in the resource-rich regions observed in this study. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2022.